Addition of one session with a specialist counselor did not increase efficacy of a family physician-led smoking cessation program. Issue 9 (September 2018) - Chung, Yi-Hsuan; Chang, Hao-Hsiang; Lu, Chia-Wen; Huang, Kuo-Chin; Guo, Fei-Ran
Objective: Higher-intensity counseling sessions increase the smoking abstinence rate. However, counselors are limited in Taiwan. This study was performed to determine whether the addition of one session with a specialist counselor increases the efficacy of a family physician-led smoking cessation program. Methods: Participants opted to either visit a family physician for brief counseling and pharmacotherapy (Po) or visit a specialist counselor for an initial session followed by a family physician for brief counseling sessions with pharmacotherapy (P+). The 7-day point prevalence (PP) rate was evaluated at weeks 12 and 24. Results: In total, 356 patients were enrolled. In the intention-to-treat analysis, the PP rate at week 12 was higher in the Po than P+ group, but there was no significant difference at week 24. In the per-protocol analysis, the PP rates at weeks 12 and 24 were not significantly different between the Po and P+ groups. The adjusted odds ratios also revealed no significant differences in either the intention-to-treat analysis or the per-protocol analysis between the two groups. Conclusion: The addition of one session with a specialist counselor had no benefit over the provision of counseling through a family physician at either 12 or 24 weeks of follow-up.